PARADOKS NARASI PENYELAMATAN KESEIMBANGAN EKOSISTEM DALAM NOVEL KAILASA KARYA JUSUF AN KAJIAN EKOKRITIK - Widya Prana Rini (POETIKA, 2018)
Abstrak             Penelitian ini membahas karya sastra yang membawa isu alam dan lingkungan tereksploitasi melalui sistem pertanian sebagai sarana merawat bumi. Perusakan lingkungan pertanian Desa Kailasa merupakan pokok permasalahan tokoh Yahya dalam penyelamatan alam dan lingkungan. Adanya gerak komunal petani yang bersifat antroposentris membuka kontestasi untuk mengakses sumber daya alam. Alam dimanfaatkan untuk mendapatkan keuntungan besar, baik pihak petani maupun pihak lain yang berkepentingan, akan tetapi tidak ada keseimbangan area pertanian jangka panjang. Melalui sudut pandang ekokritik mencermati narasi penyelamatan ekosistem dalam kontestasi kepentingan ekologis. Penelitian ini menggunakan teori ekokritik yang bertolak pada pandangan Cheryll Goltfelty. Metode yang digunakan deskriptif kualitatif. Antroposentris membuat alam dan lingkungan Kailasa terdegradasi terlihat dari manusia yang mengekploitasi alam. Teridentifikasi masyarakat Kailasa mengalami pergeseran kesadaran eko ke kesadaran ego, perubahan tersebut dilatarbelakangi oleh hidup yang berorientasi pada materi untuk kepentingan ekonomi. Ada kecenderungan yang mengarah ke kesadaran eko, terlihat pada generasi baru setelah lima belas tahun terjadi kontestasi, akan tetapi hanya berubah pada tanaman polikultur (tanaman carika). Narasi yang diuraikan terlihat mewakili pemikiran ekosentrisme yang melindungi dari kejahatan antroposentris, akan tetapi terdapat paradoks dalam memperjuangkan ekosistem yang direpresentasikan. Teridentifikasi dari masyarakat Kailasa yang tetap menggunakan cara pandang antroposentris walaupun alam dan lingkungan telah mengalami degradasi. Kata Kunci : ekologi,  ekosistem, antroposentris, ekosentris, ekstensifikas, intensifikasi, kontestasi.     Abstract This research discusses a literature that brings the issue about nature and environmental issues exploited by a farming system as means of caring for the earth. Environment represented in the novel entitled Kailasa by Jusuf AN as a form of ecology criticism and how the narrative of ecosystem rescuse in the contestation of ecological. The purpose of this research is to identify environmental damage and what attitude that should be taken as an act of saving nature and the environment in contestation of acosystem diversity. The destruction of the agricultural environment of Kailasa Village is the main issue of Yahya's character in saving nature and the environment. The anthropocentric nature of farmers' communal movements opens contestation to access natural resources. Nature is used to gain big profits, both farmers and other interested parties, but there is no balance of long-term agricultural areas. Through an ecocritical point of view, look at the narrative of saving ecosystems in the contestation of ecological interests. This research uses an ecocritism in literature that depart from the view of Cheryll Goltfelty. The method used is descriptive kualitative to dissect the problem. Anthropocentric make Kailasa nature and environment degraded which can be seen from humans who exploit nature. It is identified that there is a shift of eco to ego consiousness in Kailasa communitty while the change is motivated by material-oriented life for the sake of the economy. After nature is degraded, there is a tendency to back eco consiousness. Seen in the new generation after fifteen years of contestation, but changed on polyculture plants (carica). Narrative described appears to represent the ecocentric thinking that protects evil anthropocentris, but there is a paradox in the struggle for represented ecosystems. It is identefied from Kailasa community that they keep the antrhoposentric perspective though nature and the environment has been degraded.Keywords: ecocritic, ecosistem, antrophocentric, ecocentric, extensification, intencification, contestation.